INTERNALIZATION OF SOUL PANCA VALUES IN UNIVERSITY BUSINESS BASED ON DARUSSALAM BUSINESS UNIT OF DARUSSALAM GONTOR - Wahyu Widodo; Fajar Ari Surya Anggara (University of Darussalam Gontor, 2019)
Management functions are the basic elements that always exist and inherent in the management process that will be used as a reference by managers in carrying out activities to achieve the objectives of the world. Most management uses management functions (Planning, Organizing, Actuating and Controlling). This management principle is very widely used by small and large organizations, one of which is the University of Darussalam Business Unit which aims to further develop and manage their companies, thus almost all companies currently implementing and using management functions but, not a few also in each company that is truly competent in paying attention to management functions, as well as understanding in each individual in a company that does not understand the management functions especially for subordinates such as employees who work in the operational section. There are problems with the University of Darussalam Business Unit that the implementation of management functions in the system here is not well implemented because there are several factors that inhibit, for example employees and staff who are here usually carry out their duties according to what they see and according to them beneficial and does not cause harm to the company. Because, in addition to this company implementing management functions, this company also instills in each employee the values of five souls namely, sincerity, simplicity, self-reliance and brotherhood. The results of this study the company has implemented other companies in general, namely implementing management functions including planning, organizing, implementing and monitoring, in addition to the company implementing it all, the company has also embedded in each individual the values of the five souls that are not much even a few companies are out there that instill in each of their employees about the values of the five souls namely, sincerity, simplicity, implementation of self-reliance and brotherhood of fellow living beings..